Urea/thiourea derivatives and Zn(II)-DPA complex as receptors for anionic recognition-a brief account - Das, Priyadip; Mahato, Prasenjit; Ghosh, Amrita; Mandal, Amal Kumar; Banerjee, Tanmay; Saha, Sukdeb; Das, Amitava (Journal of Chemical Sciences, 2011)
This review covers few examples of anion complexation chemistry, with a special focus on urea/thiourea-based receptors and Zn(II)-dipicolyl amine-based receptors. This article specially focuses on structural aspects of the receptors and the anions for obtaining the desire specificity along with an efficient receptor–anion interaction. Two types of receptors have been described in this brief account; first one being the strong hydrogen bond donor urea/thiourea derivatives, which binds the anionic analytes through hydrogen bonded interactions; while, the second type of receptors are coordination complexes, where the coordination of the anion to the metal centre. In both the cases the anion binding modulate the energy gap between the highest occupied molecular orbital (HOMO) and lowest unoccupied molecular orbital (LUMO) and thereby the spectroscopic response. Appropriate choice of the signalling unit may allow probing the anion binding phenomena through visual detection.

Ultrafast electron injection, hole transfer, and charge recombination dynamics in cdse QD super-sensitized Re(I)-polypyridyl complexes with catechol and resorcinol moiety: effect of coupling - Debnath, Tushar; Maity, Partha; Banerjee, Tanmay; Das, Amitava; Ghosh, Hirendra N. (Journal of Physical Chemistry C, 2015)
Ultrafast charge-transfer dynamics have been demonstrated in CdSe quantum dots (QD) using two Re(I)-polypyridyl complexes having pendent catechol (Re1,2) and resorcinol (Re1,3) as the sensitizer molecules. The energy level diagram of CdSe QD and Re1,2 and Re1,3 sensitizer reveals that photoexcited hole of CdSe QD can be transferred to both Re1,2 and Re1,3 molecule, and photoexcited Re1,2 and Re1,3 can inject electron in the conduction band, which has been confirmed by steady-state and time-resolved photoluminescence studies with selective photoexcitation. Femtosecond transient absorption studies have been carried out to monitor charge-transfer dynamics in early time scale. Transient absorption spectra show formation of cation radicals for both Re1,2 and Re1,3 in the 550-650 nm region with a peak at 590 nm region and broad absorption in the 650-1000 nm region, which can be attributed to photoexcited electron in the conduction band of CdSe QD. Charge recombination was determined by monitoring the decay of cation radicals as well as decay of an electron and found to be slower in the Re1,3/CdSe system as compared to that of the Re1,2/CdSe system, which is due to weaker electronic coupling in the former system.